Aortic Arch Origin of the Left External Carotid Artery and Type II Proatlantal Fetal Anastomosis - Horowitz, Michael; Bansal, Surendra; Dastur, Kush (American Journal of Neuroradiology, 2003)
Summary: This case report demonstrates a rare vascular pattern of a left external carotid artery (ECA) that arises directly from the aortic arch (AA), along with a type II proatlantal-vertebral artery anastomosis. Our research shows no report of an ECA arising from the AA. This, in association with a type II proatlantal anastomosis, is interesting because of its apparent rarity.